Kikuchi-Fujimoto disease as a rare cause of cervical lymphadenopathy in 44 years old patient – a case report and review of literature - Partyka, Mariusz; Markowski, Tadeusz; Pająk, Jacek; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2014)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Kikuchi–Fujimoto disease is a rare, benign entity of unknown etiology characterized by cervical lymphadenopathy and fever state. Clinical symptoms may mimic lymphoma, and it can be pathologically misdiagnosed. The disease has been previously reported from Asian countries, but nowadays it is known, that may affect people from various countries around the world. Besides cervical lymph nodes enlargement, patients may also complain from fatigue, joint pain, arthralgia, nausea, vomiting, weight loss and diarrhea. The diagnosis is made by lymph node histologic examination. Microscopic evaluation shows paracortical foci often with necrosis and a histiocytic cellular infiltrate. There is no known effective treatment. Symptoms usually resolve spontaneously within one to four months. We report a case of Kikuchi-Fujimoto disease as a cause of cervical lymphadenopathy in a 44-yearold man and the synthetic review of the literature.